Innovation in Cocktail Party Dress design: Integrating Sekar Jagad Batik through decorative application methods - Syifa Fadhillah Masruroh; Sugiyem Sugiyem (Institut Seni Indonesia Yogyakarta, 2026)
Indonesia has many traditional fabrics throughout the country. However, over time, many people have become reluctant to wear batik clothes, particularly among younger generations who perceive traditional textiles as outdated for contemporary occasions. Therefore, the purpose of this study is to develop and socialize batik through cocktail party fashion innovations incorporating patchwork techniques, specifically using Sekar Jagad batik motifs. The methods used in this creation follow the Research and Development method for 4D models: Define, Design, Develop, and Disseminate. The design criteria emphasized wearability for semi-formal occasions, cultural representation through batik preservation, and aesthetic balance through asymmetrical composition. The result of this creation is a one-piece cocktail party dress featuring asymmetrical balance, evident in the use of a single sleeve and skirt length that differs between the front and back. Evaluation through expert validation and user testing revealed that the design successfully bridges traditional and contemporary aesthetics, with 85% of respondents expressing willingness to wear batik in cocktail settings. This study contributes to fashion design discourse by demonstrating how traditional textiles can be repositioned for modern contexts without losing cultural authenticity. The findings suggest that innovative design approaches and appropriate occasion-matching are key factors in revitalizing interest in cultural heritage textiles among contemporary consumers, offering practical implications for fashion designers and cultural preservation initiatives.